Dimethylsulfoxide exposure modulates HL-60 cell rolling interactions. Issue 4 (18th May 2012) - Gee, David J.; Wright, L. Kate; Zimmermann, Jonathan; Cole, Kayla; Soule, Karen; Ubowski, Michelle
Abstract : Human leukaemic HL-60 cells are widely used for studying interactions involving adhesion molecules [e.g. P-selectin and PSGL-1 (P-selectin glycoprotein ligand-1)] since their rolling behaviour has been shown to mimic the dynamics of leucocyte rolling in vitro . HL-60 cells are neutrophilic promyelocytes that can undergo granulocytic differentiation upon exposure to compounds such as DMSO (dimethylsulfoxide). Using a parallel plate flow chamber functionalized with recombinant P-selectin–Fc chimaera, undifferentiated and DMSO-induced (48, 72 and 96 h) HL-60 cells were assayed for rolling behaviour. We found that depending on P-selectin incubation concentration, undifferentiated cells incurred up to a 6-fold increase in rolling velocity while subjected to an approximately 10-fold increase in biologically relevant shear stress. HL-60 cells exposed to DMSO for up to 72 h incurred up to a 3-fold increase in rolling velocity over the same shear stress range. Significantly, cells exposed for up to 96 h incurred up to a 9-fold decrease in rolling velocity, compared with undifferentiated HL-60 cells. Although cell surface and nuclear morphological changes were evident upon exposure to DMSO, flow cytometric analysis revealed that PSGL-1 expression was unchanged, irrespective of treatment duration. The results suggest that DMSO-treated HL-60 cells may be problematic as a substitute for neutrophils for trafficking studies during advanced stages of the LAC (leucocyte adhesion cascade). We suggest that remodelling of the cell surface during differentiation may affect rolling behaviour and that DMSO-treated HL-60 cells would behave differently from the normal leucocytes during inflammatory response in vivo .